Morphological description and molecular characterisation of Opegaster mezcal sp. n. (Trematoda: Opecoelidae) from the Mexican Tropical Pacific - Santillan-Perez, Rodrigo I; Garcia-Varela, Martin; Aguilar-Aguilar, Rogelio (Folia parasitologica, 2025)
Opegaster Ozaki, 1928 is one of the most species-rich genera of the trematode family Opecoelidae, commonly found in marine teleost fishes. This study describes a new species of Opegaster of the intertidal fish species Labrisomus xanti Gill (Labrisomidae) (type host) and Tomicodon zebra (Jordan et Gilbert) (Gobiesocidae) from the coast of Oaxaca, Mexican Pacific. Opegaster mezcal sp. n. is characterised by the absence of papillae on the ventral sucker and the size and shape of the testes. Sequences of the D1-D3 domains from large subunit from nuclear DNA (28S) were generated for the new species and for another opecoelid species, Opecoelus adsphaericus Manter et Van Cleave, 1951. The new sequences of Opegaster mezcal sp. n. formed a clade, which is sister to O. adsphaericus. However, the phylogenetic relationships among genera of Opecoelinae remain unresolved because few species have been analysed; the addition of further taxa is necessary to better understand the evolution of the subfamily.
Keywords: Tichý oceán; taxonomy; nemoci ryb; DNA helmintů; Phylogeny; Oaxaca; Fish Diseases; Trematoda; Pacific Ocean; Trematode Infections; infekce červy třídy Trematoda; DNA, Helminth; zvířata; Mexico; Mexiko; fylogeneze; Plagiorchiida; marine fish; Animals; Digenea; Perciformes; RNA, Ribosomal, 28S; RNA ribozomální 28S